The effect of liquidity and solvency on profitability: the case of public-listed consumer product companies in Malaysia - Md Yusoff, Hanaffie (2017)
The optimal level of liquidity and solvency has been one of the key financial components essential for a smooth operation, particularly in maintaining firm performance. Successful companies will normally manipulate the two closely interrelated financial elements; liquidity and debt structure to maximize the firm’s value as well for achieving an optimal hedging strategy. Subsequently a careful attention to these two elements will help companies to achieve a lower reduction in a bankruptcy costs and to reduce the likelihood of financial distress. The illiquidity problem, unless remedied, will lead to insolvency as the business liabilities exceed its assets. For larger organizations, maintaining a good level of liquidity can ensure the stability of the business. Thus, this study sought to examine the effect of liquidity and debt on the profitability among large firms in consumer product sector in Malaysia. In order to meet the objectives a quantitative panel data methodology was employed. The data were obtained from the audited financial statements of 116 firms in consumer product sector for the period of three years (2012 – 2015). The findings reveal that liquidity in term of quick ratio has positive and significant effect on profitability. While, current ratio has negative but insignificant effect on profitability. The result further reveals that solvency has no significant effect on profitability. The study recommends that the firms can improve their performance by increasing the level of liquidity and maintaining their optimal debt structure level.